INCOME TAX INCENTIVES FOR TOURISM INDUSTRY - Widodo, Arie; Nur, Titin F (Journal of Indonesian Tourism and Policy Studies, 2021)
The COVID-19 pandemic has resulted in the collapse of the economy in all sector and countries around the world. One of the sectors that experienced a major fall was the tourism sector. The government provide income tax facilities to stimulate domestic and foreign investment. The aim of this paper is to determine the government's policy that can be utilized by business actors in the tourism sector. This study uses qualitative research methods with library research. The results of this study indicate that the real estate sector in tourism industry is one that utilizes tax facilities. This paper recommends that other sector than real estate in tourism industry given the same income tax facility.